Sharia compliance requirements framework for e-commerce systems: an exploratory study - Ribadu, Mohammed Bashir; Wan Ab. Rahman, Wan Nurhayati; Abd Ghani, Abdul Azim; Kamaruddin, Azrina; Othman, Mohd Sukki (Little Lion Scientific R&D, 2020)
There is a growing concern among Muslims over the need to ensure Sharia compliance in e-commerce transactions. Because non-conformity to Sharia principles can result in a lack of trust and a barrier for many Muslims to partake in e-commerce transactions. However, there is currently no comprehensive and clearly specified Sharia compliance requirements guideline for e-commerce systems. Therefore, a need to explore and develop a comprehensive guideline for Sharia compliance requirements in e-commerce systems. In this study, an exploratory qualitative study involving eight semi-structured interviews with Sharia compliance scholars/experts was conducted. Consequently, a conventional content analysis of data was carried out with the aid of QSR-NVivo 11. Findings from the study revealed that e-commerce is acceptable and indeed encouraged in Islam so long as it enhances the welfare of society. The fundamental Sharia compliance requirements for e-commerce are adherence to the Maqasid Sharia and the fulfillment of Islamic law of contract obligations. This requires e-commerce systems to be structured towards enhancing the welfare of the society and compliance with the form, contracting parties, and subject matter obligations of Islamic law of contract. Therefore, this study proffers a comprehensive framework of Sharia compliance requirements for e-commerce systems which provides notions that agree with the Quran, Sunnah, and e-commerce best practices. The framework provides a comprehensive but parsimonious guide that would enhance understanding and support the development of Sharia compliant e-commerce systems. Furthermore, it would guide researchers, consumers, vendors, developers, analysts, and regulators with interest in the Sharia compliance e-commerce domain.